Immunological assays of hemocytes in the Northern Quahog Mercenaria mercenaria. Issue 118 (November 2021) - Zeng, Yangqing; Huo, Yuanzi; Yang, Huiping
Abstract: The northern quahog Mercenaria mercenaria (commonly named hard clam) is an important aquaculture and fishery species along the Atlantic west coast. Environmental stresses, such as heat shock, fluctuating salinity, and harmful algal blooms are major challenges for clam aquaculture. In response to environmental stresses, hemocytes would change dynamically for defense and immunity. The goal of this study was to characterize basic immunological assays of hemocytes in the northern quahog by use of flow cytometry. The objectives were to: 1) develop a non-lethal method for hemolymph collection and dilution; 2) verify the capability of flow cytometry for hemocyte count and type identification through comparison with microscopic observation; 3) validate hemocyte viability assay based on plasma membrane integrity, and 4) develop hemocyte phagocytosis assay by use of fluorescein labeled microbeads. A non-lethal hemocyte collection method was developed using needle insertion through the ligament. Osmolality measurement of serum was the same as that of culture seawater. The pH measurement of serum (7.2) was significantly different from that of culture seawater (8.4). By microscopic observation, three types of hemocytes were identified with granulocytes, the dominant cell type (70 ± 16%), agranulocyte (14 ± 4%), and blast-like cell (16 ± 4%), and no differences were found from the measurements by flow cytometer on FSC/SSC plot (cell size/granularity). The viability of hemocytes based on plasma membrane integrity was 88 ± 6% ranging from 70 to 97% (n = 60, three populations), and viability protocol was further validated with the pre-set expected viability ( p  ≥ 0.424). Phagocytosis assay of hemocytes with fluorescence beads showed a mean capacity of 10 ± 5% (n = 60, three populations). Incubation time (up to 6 h) or bead concentrations (2:1 or 5:1 to hemocytes) did not affect the phagocytosis measurement. Overall, this study reported the basic characteristics of hemolymph (serum and hemocytes) of northern quahogs. It is expected that the assay methodologies will be applied to evaluation of hemocyte responses to environmental stresses for clam aquaculture. Highlights: A non-lethal method for hemolymph collection was developed. Hemolymph was capable of changing pH but not osmolality. Three types of hemocytes were identified by use of microscopic observation. Hemocyte cell type and concentration could collected simultaneously by FCM assays. FCM Assays of viability and phagocytosis of hemocytes was established.